2019
DOI: 10.3390/ijerph16101706
|View full text |Cite
|
Sign up to set email alerts
|

Water Productivity Evaluation under Multi-GCM Projections of Climate Change in Oases of the Heihe River Basin, Northwest China

Abstract: As the second largest inland river basin situated in the middle of the Hexi Corridor, Northwest China, the Heihe River basin (HRB) has been facing a severe water shortage problem, which seriously restricts its green and sustainable development. The evaluation of climate change impact on water productivity inferred by crop yield and actual evapotranspiration is of significant importance for water-saving in agricultural regions. In this study, the multi-model projections of climate change under the three Represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It indicated that the future climate change had a more significant impact on yield reduction under the M1WF treatment, compared with the M0WF treatment. The ET decreased by 16.1%, 14.3%, 22.3% for the M1WF treatment and 15.4%, 12.6%, 21.0% for the M0WF treatment under the RCP2.6, RCP4.5, RCP8.5, respectively [30,66,69]. The interannual variation trend of seed-maize yield under the RCP2.6 and RCP8.5 scenarios for the future 30 years were shown in Figure 8.…”
Section: Future Climate Scenariosmentioning
confidence: 95%
See 1 more Smart Citation
“…It indicated that the future climate change had a more significant impact on yield reduction under the M1WF treatment, compared with the M0WF treatment. The ET decreased by 16.1%, 14.3%, 22.3% for the M1WF treatment and 15.4%, 12.6%, 21.0% for the M0WF treatment under the RCP2.6, RCP4.5, RCP8.5, respectively [30,66,69]. The interannual variation trend of seed-maize yield under the RCP2.6 and RCP8.5 scenarios for the future 30 years were shown in Figure 8.…”
Section: Future Climate Scenariosmentioning
confidence: 95%
“…Future climate change has brought both opportunities and challenges to food production. Representative Concentration Paths (RCPs) scenarios are the most widely used method to study climate change and its impact on crop productivity [66,67]. Liu et al [66] obtained the daily precipitation, maximum air temperature and minimum air temperature under three RCPs (RCP2.6, RCP4.5, RCP8.…”
Section: Future Climate Scenariosmentioning
confidence: 99%
“…The least-square linear regression method was applied to analyze the trend of DNW at the regional and pixel scales [36,37], and the significance of regression coefficients was determined by the t-test (p-values). * indicated significant (p = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…(2019) also demonstrated that the 33 CMIP5 models evaluated in their study could capture the seasonal temperature patterns; however, most of them tended to underestimate temperatures by approximately 2.0°C. Therefore, downscaling methods and multimodel ensembles (MMEs) are of great significance for correcting biases and reducing uncertainty, as well as for retaining the valuable climate change signals of GCMs (Wang et al ., 2016; Ngai et al ., 2020; Zhang et al ., 2019; Wang et al ., 2019a; Chen et al ., 2016a; 2016b; Liu et al ., 2019). For example, Yang et al .…”
Section: Introductionmentioning
confidence: 99%